ЯМР ⁵⁷Fe в ортоферритах RFe₁-xMnxO₃ - Карначев, А.С.; Клечин, Ю.И.; Прохоров, А.А.; Соловьев, Е.Е. (Физика низких температур, 2000)
Методом спинового эха исследован спектр ЯМР ядер ⁵⁷Fe в марганецзамещенных ортоферритах Tm и Er. Показано, что эффект Яна-Теллера для примесного иона Mn³⁺ проявляется в пропорциональном усилении деформации Е-типа октаэдра Fe³⁺ -6O²⁻ . В области спин-переориентационного перехода наблюдается магнитная неэквивалентность подрешеток как ионов Fe³⁺ , так и примесных ионов Mn³⁺ . The spin echo method is used to investigate the NMR spectrum of the ⁵⁷Fe nuclei in manganese-substituted Tm and Er orthoferrites. It is shown that the Jahn–Teller effect for the Mn³⁺ impurity ion is manifested in a proportional enhancement of the EE-type deformation of the Fe³⁺–6O²⁻ octahedron. In the region of the spin-reorientation transition a magnetic inequivalence of the sublattices is observed both for the Fe³⁺ ions and for the Mn³⁺ impurity ions.